Airway, breathing, cellphone: a new vital sign? - Samuel I. Garcia; Ashley Jacobson; Gregory P. Moore; Jesse Frank; Wyatt Gifford; Samantha Johnson; Donell Lazaro-Paulina; Aidan Mullan; Alexander S. Finch (International Journal of Emergency Medicine)
Abstract Introduction In emergency medicine, triage encompasses more than the initial prioritization of treatment; it also includes decisions about the most suitable level of care and disposition for each patient. However, the increasing use of mobile technology by patients in the emergency department (ED) introduces a new factor. This study aims to explore the relationship between patients’ cellphone use at the time of initial assessment and final disposition in the ED. Methods A prospective, cross-sectional study was conducted on 292 patients who presented to the ED between 9/1/2021 and 8/9/2022. Patients were stratified into two cohorts based on their behavior during the initial assessment: actively using a cell phone (n = 32) or not using a cell phone (n = 259). Final disposition was dichotomously recorded as admission or discharge. Hospital admission, hospital observation, and admission to the ED observation unit were consolidated into the combined category of admission. Results Patients not actively using their cell phone on initial assessment exhibited a discharge rate of 64%, while those engaged with their cellphones displayed notably higher dismissal rates at 94%. The calculated odds ratio (OR) of 8.4 (95% confidence interval: 1.96-36.0, p = 0.004) underscores a significantly heightened likelihood of dismissal among individuals actively using their cellphones, suggesting a potential association between cellphone use and a reduced probability of hospital admission. Conclusion The study suggests an association between cellphone use during initial ED assessment and higher discharge rates. While this introduces a novel concept, the study’s potential contribution to more informed and efficient triage decisions warrants careful consideration in future research and clinical applications.